A Comment on "Calvert et al. (2023): Changes in Preterm Birth and Stillbirth during COVID-19 Lockdowns in 26 Countries" - Philipp Dyroff; Robert Miller (Institute for Replication (I4R), 2025)
Calvert et al. (2023) meta-analyzed effect estimates from interrupted time series (ITS) analyses of changes in preterm birth- and stillbirth rates following the first four months lockdown in various countries. Evidence for small relative reductions was reported regarding preterm birth rates in high income countries, which was not countered by an increase in stillbirth rates. This comment attempts to (recreate) reproduce these findings in population-based samples. To check robustness, effect size estimates were additionally obtained after accounting for for serial autocorrelation. Due to restricted data access, the data for reproduction were not identical to those analyzed by the original study, but were extracted from the provided time-series plots of birth rates using a Web Plot Digitizer (Rohatgi, 2024). Our results show very similar effect size estimates with ITS analysis conducted using Poisson regression and their subsequent random-effects meta-analysis. Despite of the methodological constraints arising from a lack of data openness, our reproductive analyses provide reasonable indications for the robustness of "Changes in preterm birth rate and stillbirth during COVID-19 lockdowns in 26 countries" by Calvert et al. (2023).
Keywords: 330